2023
DOI: 10.1590/0100-6991e-20233618-en
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 irritable bowel syndrome: an integrative review

Julyanne Tereza Cordeiro Silva,
Olival Cirilo Lucena da Fonseca Neto

Abstract: Introduction: the persistence of long-term symptoms of COVID-19 represents a new challenge for the medical-scientific community, it is the condition called long-term COVID-19. Irritable Bowel Syndrome (IBS) is one of the most common Disorders of the Gut-Brain Interaction and its post-infection development is already validated. According to the Rome IV criteria, it is characterized by the presence of recurrent abdominal pain, on average, at least 1 day a week in the last 3 months with onset of symptoms at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, although we did not collect data on con rmed SARS-CoV-2 infections, emerging evidence suggests that exposure to the SARS-CoV-2 virus potentially causes long-term changes in gut-brain messaging that may lead to IBS or other disordered gut-brain interactions [90,103]. Studies have shown that individuals who have previously contracted the SARS-Cov-2 virus have reported increased rates of post-infection IBS and more severe gastrointestinal issues [104,105]. Moreover, exposure to the SARS-Cov-2 virus appears to worsen preexisting symptoms for individuals already living with IBS [106].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although we did not collect data on con rmed SARS-CoV-2 infections, emerging evidence suggests that exposure to the SARS-CoV-2 virus potentially causes long-term changes in gut-brain messaging that may lead to IBS or other disordered gut-brain interactions [90,103]. Studies have shown that individuals who have previously contracted the SARS-Cov-2 virus have reported increased rates of post-infection IBS and more severe gastrointestinal issues [104,105]. Moreover, exposure to the SARS-Cov-2 virus appears to worsen preexisting symptoms for individuals already living with IBS [106].…”
Section: Discussionmentioning
confidence: 99%